Synthesis and Properties of Arylvinylidene-Bridged Triphenylamines - Hammer, Natalie; Shubina, Tatyana; Gisselbrecht, Jean-Paul; Hampel, Frank; Kivala, Milan (Journal of Organic Chemistry, 2015)
A series of arylvinylidene-bridged triphenylamines were efficiently synthesized through the thionation/Barton-Kellogg olefination sequence from their corresponding carbonyl precursors. The electrochemical investigations identified these highly distorted scaffolds as fairly strong electron donors capable of several reversible oxidation steps with the first oxidation occurring at a potential comparable to that of ferrocene for the n-hexyl-substituted diphenylvinylidene-bridged compound.
EAM Import::2019-03-12